Biotribocorrosion performance of titanium alloy Ti-6AI-4V and stainless steel 316l under simulated body environment - Alias, Juliawati (2008)
Tribological problems and corrosion degradation have been recognized as essential risks for total joint replacement, especially for metal arthroplasty. Degradation of the metals and alloys used in bearing surface in joint implants results from a combination of electrochemical and mechanical effects. By the increasing interest in metal-on-metal (MoM) joint implants, studies have been focused on their wear and corrosion behavior. A tribocorrosion test rig and sample of femoral head and acetabular cup for hip implant was designed and built to study and simulate the tribocorrosion condition of the biomaterials under two different simulated body fluids. By using this equipment, electrochemical tests have been conducted and reported in this thesis. The tribocorrosion behavior for two materials (Titanium alloy, Ti-6Al-4V and Stainless Steel 316L) have been analysed by using potentiodynamic polarization experiments. The corrosion rates of the alloys were then comparable.